Health Systems Research With Relevance To district Health Management System - Deodhar N.S (Wolters Kluwer Medknow Publications, 1993)
Three hundred women coming for early termination of pregnancy were studied to highlight their socio-demographic profiles. MTP was most common in the age group 21-30 years and 75% of them had parity of 3 or less. No method of contraception or a method with a high failure rate was used by 85.3% women. In 28.7% a previous medical termination and a history of Up to 5 abortions were obtained. The emphasis to these patients must be on education about contraception, unwanted pregnancies should be avoided but abortion should not be used as a form of planning their families.